Planificación estratégica de desarrollo productivo para mejorar los ingresos de la asociación de campesinos autónomos "vega de maíz", recinto el Vergel cantón Valencia, periodo 2012-2015 - Nieves Aguilar, Dexy Cecibel (2015)
The results of the research show that there is disagreement in partner of the Asociación de Campesinos Autónomos “Vega de Maíz”, del cantón Valencia, with the current situation, in economic matters. 93% say that the level of income earned from the sale of their products is low, high production costs and poor production. In most cases, 56% of respondents said they did not have tools and machinery needed for optimal performance. Also mention that the prices paid for their products are very low and prevent proper economic development. It is stated that the lack of training in production technology and lack of funding are also key factors that have prevented the normal development of the agricultural, livestock, swine, poultry, etc., so that polls conducted 100 % declare to agree to the implementation of a strategic plan to establish and achieve goals effectively and efficiently. Through the SWOT matrix on it was found that there are no records of strategic planning or implementing marketing and sales strategies, operational or financial, so that the development projects involving a total investment of $ 21,000.00 sought in strategies that are applied in the field of production technology to achieve increased productivity. Besides the design of projects and links MAGAP y la Universidad Técnica Estatal de Quevedo for management training, promotion and advertising of products and highly competitive prices applied to achieve an increased level of income, funding for projects production schedules with appropriate interest rates through the National Bank of Development, strategies that support the achievement of high levels of profitability.